Propensity for participative decision making (PPDM) in Turkey and the USA. (1st January 2012) - Parnell, John A.; Koseoglu, Mehmet Ali; Dent, Eric B.
Increased subordinate participation in management decisions has been a recognised trend in both private and public organisations in many western nations. Less is known about such practices in other parts of the world, however, especially in emerging countries. This study assesses similarities and differences between US and Turkish managers with regard to propensity for participative decision making (PPDM). The first hypothesis tests the validity of the PPDM scale among a sample of Turkish managers, and was supported. The second hypothesis examines whether US managers report higher levels of participation with respect to the four dimensions of organisational effectiveness, power, culture, and commitment. Surprisingly, the Turkish managers reported higher levels of participation in the first three dimensions, with no statistical difference with the US managers on commitment. Other findings are discussed and directions for future research are also presented.